2018
DOI: 10.7759/cureus.2598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CyberKnife Radiosurgery for Recurrent Trigeminal Neuralgia

Abstract: Stereotactic radiosurgery (SRS) has evolved as an accepted treatment for medication resistant trigeminal neuralgia. Initial results are very good but follow-up over three to five years shows a gradual return of pain in up to 50% of treated patients, often requiring further treatment. The results with repeat SRS using the isocentric Gamma Knife (GK) (Elekta, Stockholm, Sweden), especially in patients having initially good results, are very similar to the outcomes after the initial treatment although there is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…This is an aspect to take into account in this entity, since a previous history of invasive surgical interventions may diminish the therapeutic efficacy of CyberKnife 11 . The expected risk or complication of this treatment is facial numbness in 4.3-12.0% of cases, which can best be described as a side effect positively associated with effective pain relief and directly proportional to the amount of Gy applied 11 , 13 . So far, no mortality has been attributed to CyberKnife in any study, and among other complications found are cerebral edema, radionecrosis, hemiparesis, and dysesthesia 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an aspect to take into account in this entity, since a previous history of invasive surgical interventions may diminish the therapeutic efficacy of CyberKnife 11 . The expected risk or complication of this treatment is facial numbness in 4.3-12.0% of cases, which can best be described as a side effect positively associated with effective pain relief and directly proportional to the amount of Gy applied 11 , 13 . So far, no mortality has been attributed to CyberKnife in any study, and among other complications found are cerebral edema, radionecrosis, hemiparesis, and dysesthesia 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Se desestimaron otras opciones como neurolisis del ganglio de gaser y rizotomía, por la posibilidad de un manejo menos invasivo como la radiocirugía, que en casos persistentes de neuralgia del trigémino, forman parte de las opciones dentro de las nuevas guías 3 , 11 , 13 , 14 , 16 por poseer mayor efectividad en eliminación del dolor 3 , 6 y menor probabilidad de complicaciones como: hipoacusia, hipoestesia facial, fístula del líquido cefalorraquídeo o hemorragia postquirúrgica 2 . Por tal motivo con idea de integrar nuevas alternativas y lograr obtener resultados diferentes, se determinó la realización de radiocirugía por CyberKnife, teniendo en cuenta otros reportes de casos y estudios que constatan sus beneficios 3 , 11 - 16 , 19 , además de los antecedentes de diversos procedimientos fallidos realizados a la paciente como acupuntura, medicación exagerada, descompresión microvascular y su sintomatología dolorosa que afectaba la parte social y mental.…”
Section: Discussionunclassified
“…Currently, the cone-based SRS using the specialized machines such as GammaKnife, CyberKnife, and other LINACs remains the standard practice for the treatment of small intracranial lesions such as trigeminal neuralgia (TGN). [10][11][12][13] However, it poses several challenges; need of (1) a cone-specific dose calculation, (2) ensuring geometric precision for each cone collimating system, (3) rigorous patient-specific quality assurance (QA), and (4) avoidance of collision for cone-based arcs. It should be noted that a well-defined spherical or ellipsoidal dose distribution along with a high mechanical precision in dose delivery is required for such treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of systematic reviews and retrospective series report relevant findings. 911 As with initial RS for TN, only a limited number of studies report CKRS in the setting of re-treatment. 7,11…”
Section: Introductionmentioning
confidence: 99%
“…911 As with initial RS for TN, only a limited number of studies report CKRS in the setting of re-treatment. 7,11…”
Section: Introductionmentioning
confidence: 99%